Uruguay : women in culture, business, & travel. (Women in culture, business, & travel, 2010)
Women often occupy different roles in a foreign culture. Avoid offensive assumptions and behavior by understanding the position of women in Uruguayan society: their legal rights; access to education and health care; workforce participation; and their dating, marriage, and family life.